EFEKTIFITAS TANAMAN SERAI (Andropogan nardus L.) SEBAGAI TANAMAN PENOLAK Liriomyza sp.(Diptera : Agromizidae) PADA PERTANAMAN BAWANG MERAH LEMBAH PAL - Lamba, Ariana; Pasaru, Flora; Shahabuddin, Shahabuddin (AGROTEKBIS, 2017)
The research objective was to determine the effectiveness of the lemongrass plant (Andropogannardus L.) as a repellent pest plant against Liriomyza sp. At shallot cropping in Palu Valley. This study used a randomized block design within which treatments included plantingÂ  lemongrass plant (PLP) at four weeks (PLP 4), two weeks before (PLP 2) and at the same time (PLP 0) of the shallot crop was planted, as well asÂ  control (with no lemongrass planting). Variables observed were the populations of adult Liriomyza sp. and the attack rate of Liriomyza sp. as well as the crop production. The results showed that five and six weeks after the shallots were planted, the population of adult and the attack rate of Liriomyza sp. were lower in the PLP 4 than in the PLP 2, PLP 0 and control treatments. The treatment plant as a crop repellent lemongrass does not affect the production of onion valley hammer.Attack rate, repellent plants, Liriomyza sp. imago